1995
DOI: 10.1177/036354659502300516
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Measurement of Patellar Mobility

Abstract: To provide an objective analysis of medial and lateral patellofemoral laxity, we examined 94 uninjured athletic subjects and 22 patients with unilateral lateral patellar dislocation. We developed an instrument to measure the compliance of the medial and lateral patellar restraints. The instrument recorded the force-displacement relationship as the patella was pushed medially and laterally. Subtracting the medial displacement from the lateral displacement at a given force level allowed the tester to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 33 publications
1
66
1
4
Order By: Relevance
“…This concept is consistent with research findings and treatment recommendations for the knee joint, which houses the largest sesamoid in the body (the patella). 2,20,37,44 The experimental group also had statistically significant improvement in flexor hallucis strength while the control group did not. There are several explanations for this difference.…”
Section: Discussionmentioning
confidence: 85%
“…This concept is consistent with research findings and treatment recommendations for the knee joint, which houses the largest sesamoid in the body (the patella). 2,20,37,44 The experimental group also had statistically significant improvement in flexor hallucis strength while the control group did not. There are several explanations for this difference.…”
Section: Discussionmentioning
confidence: 85%
“…Several previous studies investigating force-displacement curves for both spinal accessory movements (Lee & Svensson 1990;Lee & Evans 1992;Latimer et al 1996dLatimer et al , 1997 and peripheral accessory movements (Yoon & Mansour 1982;Clark et al 1987;Luster et al 1990;Watson & Andrews 1991;Skalley et al 1993;Fithian et al 1995;Maitland & Kawchuk 1997) have also shown that resistance occurs immediately the testing force is applied. This is not surprising as it follows the physical law that when a force is applied there is an equal and opposite force.…”
Section: Discussionmentioning
confidence: 93%
“…The Q angle has been subjected to a radical modification in order to play a positive clinical tool and provide a certain clinical value. Fithian et al has proposed a modified Q angle by measuring it in 30° of knee flexion with the patella manually reduced into the trochlea 21 . By analyzing all subject knees into different subtypes of patellar displacement to reveal an association between Q angle and patellar alignment and to endorse the Q angle with a promising pathognomonic value among PFPS patients or knees of less displaced patellae, the current study would help motivate further revision and endorsement of the Q angle in regard.…”
Section: Discussionmentioning
confidence: 99%